Rationality of Informal Sector Vendor Groups in Maintaining Business - Santoso, Slamet; Wafirotin, Khusnatul Zulfa; Cahyono, Yeni; Wijayanti, Iin; Ayutika, Riza Dessy Nila (Universitas Muhammadiyah Ponorogo, 2025)
Informal sector vendors have now penetrated every city. This phenomenon is interesting to study further, especially their rational efforts to maintain their business. This study aims to determine how the rationality of informal sector vendor groups works in running and maintaining their business. Studying rationality becomes important because, for base consideration, it is important that they run in the group so that they are capable of maintaining their efforts until the moment. This study uses a social definition paradigm with a qualitative approach and a case study research type. The data collection methods used are in-depth interviews and observations. Data analysis uses interactive model analysis with data validity checks by triangulation. The study results show that informal sector vendors do not run informal sector vendors individually and separately, but their vendors are run in groups. The existence of these groups is important because they can help each other or help each other, support each other's vendors by maintaining harmony and mutual respect between each other so that they can run and maintain their business. The rationality of informal sector vendors is included in the type of value rational action (Werk Rational).